Drought response of PM21 Megathyrsus maximus genotypes of tropical forages - Barbosa, Norma; Garzon, Maria Jose (2025)
This study evaluated 80 genotypes of Megathyrsus maximus grasses PM21 population, alongside three well-characterized checks known for their ability to escape or avoid drought. The plants were grown for 3 weeks under both well-watered and water-deficit conditions in long tubes to assess root length. We hypothesized that plants with deeper roots would exhibit higher productivity under drought conditions.